Prospect Of Performance Development Sharia Mutual Funds In The Indonesian Capital Market - Syahputra, Aprilian Dwi (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2024)
Investment is one of the efforts to overcome the problems that occur in the Indonesian economy. There are many investment sectors that can be used to invest excess capital or assets. Islamic mutual funds as a form of investment institution innovation from conventional mutual funds have fundamental differences in the management of investor funds, which must be guided by and must not conflict with sharia values. Several mutual fund studies in Indonesia mention that the prospect of developing Islamic mutual funds is experiencing quite good growth both in terms of performance and program. This research uses literature research method. The purpose of this study is to analyze the prospects for the development and growth of Islamic mutual funds in Indonesia. From several previous studies, it is concluded that the development of Islamic mutual funds also has promising economic prospects in the future. Factors that can hinder the development of Islamic mutual funds are caused by the literacy of the general public regarding Islamic mutual funds, where people assume that Islamic mutual fund investments are only for Muslims so that in general people are more likely to choose conventional mutual fund investments when viewed in terms of fund management experience.